Navigating the Political Economy Trilemma in the ASEAN Economic Community: A Legal Perspective - Abdillah, Ali (Journal of Indonesian Legal Studies, 2025)
This article examines the challenges impeding effective regional economic integration in ASEAN through the ASEAN Economic Community (AEC). It does so by using Dani Rodrik's political economy trilemma theory as a conceptual framework. This analysis shows that ASEAN is currently stuck in the trilemma between hyperglobalization, nation-state, and democratic politics, leading to ineffective regional economic integration. Rodrik proposes that the solution to the political economy trilemma is not maximum globalization or economic integration but, instead, a smart form of globalization or of economic integration. This “smart form” contains a thin layer of international law that facilitates flexibility towards a country to maintain its national sovereignty. However, this article hypothesizes that this solution is underdeveloped as it lacks the legal details required to implement the smart form of globalization or economic integration. Specifically, the political economy trilemma framework does not provide the necessary legal mechanisms required to implement safeguard measures effectively and to navigate the principle of non-interference in intergovernmental contexts like ASEAN. This article aims to fill the legal gap by analyzing the legal dimension of the AEC through the lens of Rodrik's political economy trilemma. Thus, by applying Rodrik’s political economy trilemma, this article provides legal insights as thought directions for operationalizing the smart legal framework required to address the political economy trilemma, such as moving beyond the principle of non-interference, reforming the AEC institutional framework, and establishing safeguard measures within the AEC legal framework.